1998
DOI: 10.1016/s0014-5793(98)00420-7
|View full text |Cite
|
Sign up to set email alerts
|

Diadenosine oligophosphates (ApnA), a novel class of signalling molecules?

Abstract: The diadenosine oligophosphates (Ap n A) were discovered in the mid-sixties in the course of studies on aminoacyltRNA synthetases (aaRS). Now, more than 30 years later, about 300 papers have been published around these substances in attempt to decipher their role in cells. Recently, Ap n A have emerged as intracellular and extracellular signalling molecules implicated in the maintenance and regulation of vital cellular functions and become considered as second messengers. Great variety of physiological and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
145
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(150 citation statements)
references
References 80 publications
3
145
0
2
Order By: Relevance
“…2B). These hypothetical genes might be related to metabolism of other ribonucleotide analogs, such as diadenosine oligophosphates (43).…”
Section: Discussionmentioning
confidence: 99%
“…2B). These hypothetical genes might be related to metabolism of other ribonucleotide analogs, such as diadenosine oligophosphates (43).…”
Section: Discussionmentioning
confidence: 99%
“…In Escherichia coli, cell division is associated with an increase in the concentration of Ap 4 A. In mammalian cells, Ap 3 A and Ap 4 A have been implicated in inhibition of ATP-sensitive potassium channels and regulation of intracellular levels of Ca 2 þ (Kisselev et al, 1998), and when added to the medium at 10 mM, Ap 4 A induced apoptosis in cultures of human HL60, U937, Jurkat, and mouse VMRO cells (Vartanian et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to dephosphorylating diphosphoinositol polyphosphates, DIPP also actively hydrolyzes diadenosine 5Ј ,5ЈЈЈ-P -hexaphosphate (Ap 6 A) (Yang et al 1999), a group of putative signaling molecules implicated in regulating a diverse array of cellular functions (Kisselev et al 1998;Miras-Portugal et al 1998). It has been reported that the levels of diadenosine polyphosphates were increased in response to heat shock and oxidative stress (Baker and Jacobson 1986).…”
Section: Discussionmentioning
confidence: 99%